2014
DOI: 10.1007/s10461-014-0908-7
|View full text |Cite
|
Sign up to set email alerts
|

HIV Stigma as a Barrier to Retention in HIV Care at a General Hospital in Lima, Peru: A Case–Control Study

Abstract: HIV stigma as a barrier to retention in HIV care has not been well-studied outside the United States. We conducted a case-control study in Lima, Peru to examine this issue. Cases were out-of-care for ≥12 months (n=66) and controls were recruited from patients in active care presenting for a clinic visit (n=110). A previously validated HIV stigma scale with four domains was used. Associations between being out-of-care and each stigma domain were assessed using multivariable logistic regression. Stigma scores we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 51 publications
2
37
2
5
Order By: Relevance
“…Importantly, during the first year after diagnosis, 37% of PLWH experience depressive symptoms and 54% report HIV-related psychological distress (713). A major contributing factor to mental health outcomes is HIV-related stigma (1423). HIV-related stigma is generally understood within Goffman’s seminal work (24), wherein stigma is defined as “an attribute that is significantly discrediting” to societies.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, during the first year after diagnosis, 37% of PLWH experience depressive symptoms and 54% report HIV-related psychological distress (713). A major contributing factor to mental health outcomes is HIV-related stigma (1423). HIV-related stigma is generally understood within Goffman’s seminal work (24), wherein stigma is defined as “an attribute that is significantly discrediting” to societies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that improving knowledge of HIV care as an intervention could influence the retention of HIV positive people[51,52]. Furthermore, according to the seek-test-treat-succeed model, literate HIV infected people[53] have the capacity to provide almost 40% of HIV service-related tasks[54] and could lead to retention and re-engagement into care[47].…”
Section: Discussionmentioning
confidence: 99%
“…Barriers at the community level include stigma and discrimination, 16,7476,81,89,9497 limited ART knowledge within the community, lack of community involvement in program planning, and lack of community mobilization around ART. 74,78,94,96 Inequitable gender norms, including community stereotypes of masculinity and femininity are key determinants of delayed linkage to care and treatment.…”
Section: Linkage To Care and Treatmentmentioning
confidence: 99%
“…16,25,81,87,89,97,105110 Interventions engaging traditional practitioners and faith healers yielded mixed results. Although 1 study 111 demonstrated that training traditional healers led to increased referral rates in Mozambique, others 112114 did not find such an effect.…”
Section: Linkage To Care and Treatmentmentioning
confidence: 99%